KOMPARASI PENGGUNAAN METODE THE POWER OF TWO DAN TALKING STICK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADIS - Zain, Faza Faizatuz; Mashuri, Imam; Erlangga, Moh. (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
In this study, the researcher describes a comparison or comparison between the learning of class VII students who have been involved in two different learning methods, namely The Power of Two and Talking Stick at MTs Negeri 5 Banyuwangi, which is located in Cluring District. Then to find out which one is superior between student learning outcomes and learning using The Power of Two and Talking Stick methods. This research is a descriptive quantitative research. With a population of class VII students totaling 143 students. Meanwhile, the sample in this study was 42 children who were members of class VII A and VII B. The main data in this study were obtained based on the test instrument given by the researcher to the sample students. In addition, researchers also used other research instruments in the form of interviews and observations as additional data. Data on student learning outcomes obtained from tests conducted by researchers were then tested for validity (validity) and reliability (reliability) to determine whether the data obtained by researchers could be further analyzed. Once declared valid and reliable. Homogeneity and normality tests were conducted to determine whether the data experienced a normal distribution and had the same or homogeneous data variance. Furthermore, to find out the comparison between student learning outcomes between the application of The Power of Two method with Talking Stick, a hypothesis test was carried out in the form of a t-test (t-test). The results of this study indicate that there is an influence between the methods on the paired sample t-test which shows the t-value of the two methods on learning outcomes which is higher than the t-table value. The results of the t-test indicate that the t-count value of student learning outcomes after learning with The Power of Two method is -5.405 while for post-learning student learning outcomes using the Talking Stick method is -9.477, then from this study it can also be concluded that the score student learning outcomes influenced by the Talking Stick method were higher than student learning outcomes influenced by The Power of Two method (-9.477>-5.405). Thus it is concluded that in this study the alternative hypothesis (Ha) is accepted while the null hypothesis (H0) is rejected. Keywords: Comparison, The Power of Two, Talking Stick, Method, Learning Outcomes